Effects of dietary curcumin levels on the growth, intestinal morphology and microbiota, waste production and feed costs of golden pompano Trachinotus ovatus - Xing Ren; Xiaojie Lu; Yueyuan Tan; Jia Xu; Fan Wang; Yanqiu Zhang; Huaiyi Fang; Aiping Feng; Enge Xie; Jianqiang Song (Aquaculture Reports, 2024)
This study investigated the effects of dietary curcumin levels on the growth, feed utilization, body composition, waste production, fishery resource input, feed costs, intestinal morphology and intestinal microbiota in golden pompano. A fishmeal-based diet was supplemented with different amounts of curcumin to create diets R (0 g/kg), S1 (0.5 g/kg), S2 (1 g/kg), S3 (2 g/kg), S4 (4 g/kg), S5 (8 g/kg), and S6 (10 g/kg). No statistically differences were found in feed conversion ratio, retention efficiencies of nitrogen and phosphorus, condition factor, viscerasomatic index, body proximate composition, and waste output of carbon, nitrogen and phosphorus among different treatments. Values of final body weight (FBW) and weight gain in treatments S1-S6 tended to be higher than in treatment R, and the highest values of FBW and weight gain were found in treatment S3. Higher economic conversion ratio (ECR) was found in treatments S4-S6 than that in treatment R, while no significant difference was found in ECR between treatments S1-S3 and treatment R. Treatments S3 and S6 exhibited higher intestinal villus height compared with treatment R. Treatments S2 and S3 exhibited comparable intestinal villus height, goblet cells number, and ratio of intestinal villus height to crypt depth compared with treatment R. Treatments S2 and S3 showed higher relative abundance of the genus Ralstonia and Paraclostridium, and the species of Ralstonia_insidiosa and Paraclostridium_bifermentans_ATCC_638. These results indicate that suitable dietary curcumin has beneficial effects on the growth, intestinal morphological structure, and intestinal probiotics abundance in golden pompano.